Cardiac remodeling in a rat model of diet-induced obesity - Leopoldo, Andre Soares; Sugizaki, Mario Matheus; Lima-Leopoldo, Ana Paula; do Nascimento, Andre Ferreira; Melo Luvizotto, Renata de Azevedo; Salome de Campos, Dijon Henrique; Okoshi, Katashi [UNESP]; Dal Pai-Silva, Maeli [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Elsevier B.V., 2010)
The mechanisms by which diet-induced obesity cause remodeling and cardiac dysfunction are still unknown. Interstitial collagen and myocardial ultrastructure are important in the development of left ventricular hypertrophy, and are essential to the adaptive and maladaptive changes associated with obesity. Thus, the accumulation of collagen and ultrastructural damage may contribute to cardiac dysfunction in obesity. The purpose of the present study was to investigate cardiac function in a rat model of diet-induced obesity and to test the hypothesis that cardiac dysfunction induced by obesity is related to myocardial collagen deposition and ultrastructural damage. Thirty-day-old male Wistar rats were fed standard (control [C]) and hypercaloric diets (obese [Ob]) for 15 weeks. Cardiac function was evaluated by echocardiogram and isolated left ventricle papillary muscle. Cardiac morphology was assessed by histology and electron microscopy. Compared with C rats, Ob rats had increased body fat, systolic blood pressure and area under the curve for glucose, leptin and insulin plasma concentrations. Echocardiographic indexes indicated that Ob rats had increased left ventricular mass, increased systolic stress and depressed systolic function. Analysis of the isolated papillary muscle was consistent with higher myocardial stiffness in Ob compared with C rats. The Ob rats had an increase in myocardial collagen and marked ultrastructural changes compared with C rats. Obesity promotes pathological cardiac remodeling with systolic dysfunction and an increase in myocardial stiffness, which, in turn, is probably related to afterload elevation and cardiac fibrosis. Obesity also causes damage to myocardial ultrastructure, but its effect on myocardial function needs to be further clarified.
Keywords: Collagen; Echocardiography; Myocardial ultrastructure; Obesity; Papillary muscle; Rats